The modified Stack procedure for central slip reconstruction: a case series - James Warbrick-Smith; Holly Morris; Shirley Collocott; Amy Wang; Karen L Smith (Australasian Journal of Plastic Surgery)
There are many surgical techniques for reconstruction of the divided or incompetent central slip. Most rely upon postoperative immobilisation to protect the repair. We present our experience using a distally based flexor digitorum superficialis slip to reconstruct the central slip and allow early mobilisation in five patients with intact preoperative intrinsic function. Post-treatment, a mean recovery of 65 degrees of active extension was achieved, albeit at the cost of a mean 22-degree loss of active flexion. We suggest this relatively easy technique provides a useful surgical option in the management of this difficult problem.